Case Report: Pediatric Recurrent Acute Liver Failure Caused by Neuroblastoma Amplified Sequence (NBAS) Gene Mutations - Jiang, Bingxin; Xiao, Fangfei; Li, Xiaolu; Xiao, Yongmei; Wang, Yizhong; Zhang, Ting (Frontiers in Pediatrics, 2021)
Acute liver failure (ALF) in childhood is a rapidly progressive, potentially life-threatening condition that occurs in previously healthy children of all ages. However, the etiology of approximately 50% of cases with pediatric ALF remains unknown. We herein report a 4-year-old Chinese girl with recurrent ALF (RALF) due to a mutation in the neuroblastoma amplified sequence (NBAS) gene. The patient had suffered from multiple episodes of fever-related ALF since early childhood. She had also suffered with acute kidney injury, hypertension, mild pulmonary hypertension, pleural effusion, and hypothyroidism. A novel compound heterozygote mutation, c.3596G> A (p.C1199Y)/ex.9del (p.216-248del), in the NBAS gene was identified by whole-exome sequencing (WES). The missense mutation c.3596G> A (p. C1199Y) was inherited from her father, and ex.9del (p.216-248del) was inherited from her mother. The patient was managed with intensive treatments, such as renal replacement therapy (CRRT), intravenous antibiotics, and glucose infusion, and was discharged after full recovery. We identified a novel compound heterozygote mutation in the NBAS gene that caused fever-related RALF in a Chinese child, which further expands the mutational spectrum of NBAS.